Chiral drugs chemistry and biological action - Lin, Guo-Qiang, 1943-; You, Qi-Dong; Cheng, Jie-Fei (Wiley, 2011)
"This book overviews chiral drugs and their impact in the pharmaceutical industry. The chapters detail basics and trends in chiral drug discovery and development, as well as techniques / skills and trends of asymmetric synthesis. The first section introduces the general concept of chirality and its impact on the drug discovery and development. This part includes history of chiral drug development, key technologies for preparation of chiral drugs, and industrial applications of chiral technologies"--Provided by publisher.